The brain-gut-microbiota axis in the treatment of neurologic and psychiatric disorders - Maria Fernanda Naufel; Giselle de Martin Truzzi; Caroline Marcantonio Ferreira; Fernando Morgadinho Santos Coelho (Arquivos de Neuro-Psiquiatria)
The human gut microbiota is a complex ecosystem made of trillions of microorganisms. The composition can be affected by diet, metabolism, age, geography, stress, seasons, temperature, sleep, and medications. The increasing evidence about the existence of a close and bi-directional correlation between the gut microbiota and the brain indicates that intestinal imbalance may play a vital role in the development, function, and disorders of the central nervous system. The mechanisms of interaction between the gut-microbiota on neuronal activity are widely discussed. Several potential pathways are involved with the brain-gut-microbiota axis, including the vagus nerve, endocrine, immune, and biochemical pathways. Gut dysbiosis has been linked to neurological disorders in different ways that involve activation of the hypothalamic-pituitary-adrenal axis, imbalance in neurotransmitter release, systemic inflammation, and increase in the permeability of the intestinal and the blood-brain barrier. Mental and neurological diseases have become more prevalent during the coronavirus disease 2019pandemic and are an essential issue in public health globally. Understanding the importance of diagnosing, preventing, and treating dysbiosis is critical because gut microbial imbalance is a significant risk factor for these disorders. This review summarizes evidence demonstrating the influence of gut dysbiosis on mental and neurological disorders.